A comparison of the effect of riveting and cold expansion on the strain distribution and fatigue performance of fiber metal laminates. (April 2014) - Backman, David; Patterson, Eann A
Fatigue tests carried out on three configurations (unexpanded, cold expanded and riveted) of fiber metal laminate material clearly demonstrated the beneficial effect of riveting compared to cold expansion in zero load transfer joints, for an approximately equivalent level of interference. Digital image correlation was used to measure the in-plane surface strain on cold expanded and riveted coupons during fatigue loading, and for the first time, digital image correlation was combined with pressure sensitive films to measure the strains resulting from the application of the rivet, including those under the rivet head. A comparison of the resultant strain field showed that the application of a rivet significantly reduces the stress concentration at the central hole and is effective in extending fatigue life. Some rivet heads were removed by milling, and the results from subsequent fatigue tests were used together with closed-form calculations to explain the findings of this study. It was concluded that the beneficial effect of riveting was less as a result of interference hole filling on the part of the rivet shank, but more a combination of the effect of interference and compression through the joint thickness.